An updated review of case–control studies of lung cancer and indoor radon-Is indoor radon the risk factor for lung cancer? - Sheen, Seungsoo (Ann Occup Environ Med, 2016)
Lung cancer is a leading cause of cancer-related death in the world. Smoking is definitely the most important risk factor for lung cancer. Radon ((222)Rn) is a natural gas produced from radium ((226)Ra) in the decay series of uranium ((238)U). Radon exposure is the second most common cause of lung cancer and the first risk factor for lung cancer in never-smokers. Case–control studies have provided epidemiological evidence of the causative relationship between indoor radon exposure and lung cancer. Twenty-four case–control study papers were found by our search strategy from the PubMed database. Among them, seven studies showed that indoor radon has a statistically significant association with lung cancer. The studies performed in radon-prone areas showed a more positive association between radon and lung cancer. Reviewed papers had inconsistent results on the dose–response relationship between indoor radon and lung cancer risk. Further refined case–control studies will be required to evaluate the relationship between radon and lung cancer. Sufficient study sample size, proper interview methods, valid and precise indoor radon measurement, wide range of indoor radon, and appropriate control of confounders such as smoking status should be considered in further case–control studies.